Endogenous Preferences: The Cultural Consequences of Markets and Other Economic Institutions - Bowles, Samuel (Journal of Economic Literature, 2016)
Drawing on experimental economics, anthropology, social psychology, sociology, history, the theory of cultural evolution as well as more conventional economic sources, I review models and evidence concerning the impact of economic institutions on preferences, broadly construed. I identify a number of ways in which the form of economic organization of a society appears to influence the process of human development by shaping tastes, the framing of choice situations, psychological dispositions, values, and other determinants of individual behavior. I conclude by commenting on some implications for economic theory and policy analysis.